The alteration of interspecific interaction responded to various relative sowing time in wheat/maize intercropping - Sun, Jun-Wei; Zhu, Ying-An; Pang, Yu; Liu, Chen-Xi; Sun, Jian-Hao; Zhang, Wei-Ping; Li, Long; Liu, Yi-Xiang (Frontiers in Plant Science, 2024)
An interspecific interaction is an important reason for the yield advantage of interspecific cropping compared with sole cropping, and the relative sowing time of species is an important factor affecting interspecific competitiveness. Our purpose was to explore the effects of different relative sowing times on the interspecific competition-recovery phenomenon in wheat and maize intercropping systems. Three planting methods (wheat/maize intercropping, wheat and maize sole cropping) and different relative sowing times of wheat were used to carry out field experiments over two years. Sequential harvest of subplots was performed between 3 and 6 times, and the biomass data were fitted to logistic growth model.Delaying the sowing time of wheat reduced the wheat yield, biomass and nutrient acquisition and increased those of maize, but wheat still had an intercropping advantage during the co-growth period. At the same time, the nutrient acquisition of maize was still inhibited, but its recovery growth advanced.Changing the relative sowing time of wheat significantly changed the maximum instantaneous growth rates of wheat and maize. Delaying the relative sowing time of wheat significantly reduced its maximum instantaneous growth rate, while enhancing that of maize, leading to a balanced mutual benefit. Delaying the sowing time of wheat to the same sowing time as maize will change wheat/maize intercropping from asymmetrical interspecific facilitation to symmetrical interspecific facilitation. However, in this case, intercropped wheat still had an interspecific competitive advantage in the co-growth stage, and intercropped maize still underwent a competition-recovery process.